PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS EDUCAPLAY MATERI KEANEKARAGAMAN HAYATI - Deanda Absyarina; Nita Karmila; Ade Wiajaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Deanda Absyarina. 037121119. Development of Educaplay-Based Learning Evaluation on Biodiversity Material. Development of Educaplay-Based Evaluation on Biodiversity Material functions as a tool for teachers in the teaching process. This study is to produce a learning evaluation product based on Educaplay on Biodiversity material, in class IV-A SDN Polisi 01 with a total of 29 students. The development of this product uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study began by conducting a needs analysis, curriculum analysis, student analysis and product design. Then develop a learning evaluation product, conduct expert validation and then conduct a limited trial of learning evaluation using Educaplay on Biodiversity material on predetermined respondents. The results of the validation study from material experts, language experts and media experts showed that the learning evaluation using Educaplay was very valid and very feasible to use with an average percentage of 85%. In the trial phase, it was limited to 29 students who gave very good and very interesting respondents to use by obtaining an average percentage of 92.13%. Based on the results of the study, it can be concluded that the evaluation of learning using Educaplay on the Biodiversity material developed in this study was proven to be valid, easy and interesting for students to use and worthy of being studied.